Effect of cempedak addition before and after fermentation on the quality of goat milk yoghurt - Arif Ismanto; Mirna Mualim; Amani Aldiyanti; Fadhil Muharram; Muhammad Rizki Fadillah; Yunda Shasa Paradilla; Farah diba 'izzati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Goat milk yoghurt has considerable potential as a functional dairy product because of its high nutritional value and digestibility. However, its distinctive goaty aroma may reduce consumer acceptance. Incorporating cempedak fruit (Artocarpus champeden), known for its strong and distinctive aroma, is anticipated to enhance the sensory quality of goat milk yoghurt. This study aimed to evaluate the effect of adding cempedak before and after fermentation on the physical properties (pH and color) and organoleptic characteristics of goat milk yoghurt. The experiment consisted of two treatments with four replicates: addition of cempedak after fermentation (A) and addition before fermentation (B). The physical properties were analyzed using instrumental measurements, and organoleptic data were evaluated using the Wilcoxon signed-rank test. The results showed that Treatment A produced a higher pH value than treatment B. In terms of color, treatment A exhibited higher lightness (L*), whereas treatment B exhibited higher redness (a*) and yellowness (b*). Organoleptic evaluation indicated that the yoghurt with cempedak added after fermentation was preferred by panelists in terms of taste, aroma, texture, and color. In conclusion, the timing of cempedak addition significantly influenced both the physicochemical and sensory qualities of goat milk yoghurt, with post-fermentation addition providing better overall acceptability.